Mutations associated with Dent's disease affect gating and voltage dependence of the human anion/proton exchanger ClC-5 - Alekov, Alexi K. (Frontiers in Physiology, 2015)
Dent’s disease is associated with impaired renal endocytosis and endosomal acidification. It is linked to mutations in the membrane chloride/proton exchanger ClC-5, however, a direct link between localization in the protein and functional phenotype of the mutants has not been established until now. Here, two Dent’s disease mutations, G212A and E267A, were investigated using heterologous expression in HEK293T cells, patch-clamp measurements and confocal imaging. WT and, mutant ClC-5 exhibited mixed cell membrane and vesicular distribution. Reduced ion currents were measured for both mutants and both exhibited reduced capability to support endosomal acidification. Functionally, mutation G212A was capable of mediating anion/proton antiport but dramatically shifted the activation of ClC-5 towards more depolarized potentials. The shift can be explained by impeded movements of the neighboring gating glutamate Gluext, a residue that confers major part of the voltage dependence of ClC-5 and serves as a gate at the extracellular entrance of the anion transport pathway. Cell surface abundance of E267A was reduced by 50% but also dramatically increased gating currents were detected for this mutant and accordingly reduced probability to undergoing cycles associated with electrogenic ion transport. Structurally, the gating alternations correlate to the proximity of E267A to the proton glutamate Gluin that serves as intracellular gate in the proton transport pathway and regulates the open probability of ClC-5. Remarkably, two other mammalian isoforms, ClC-3 and ClC-4, also differ from ClC-5 in gating characteristics affected by the here investigated disease-causing mutations. This evolutionary specialization, together with the functional defects arising from mutations G212A and E267A, demonstrate that the complex gating behavior exhibited by most of the mammalian CLC transporters is an important determinant of their cellular function.